Building Bridges to Reconciliation: A Life Story of an Atikamekw School Principal - Deschênes, Emilie; Sasseville Quoquochi, Pascal (Journal of the Canadian Association for Curriculum Studies, 2023)
The implementation of Truth and Reconciliation Commission’s (TRC) Calls to Action is a challenge for the principals of Indigenous schools where non-Indigenous teachers and Indigenous teachers collaborate. This context implies a constant reflection on the means to undertake these actions. In the context of an exploratory qualitative research in these schools, 23 school principals were interviewed. Following these meetings, for the purposes of this contribution, a testimony was retained and delivered as a story; it focused more specifically on the implementation of actions that promote the creation of bridges between stakeholders in the context of the publication of the TRC report. For Indigenous people, storytelling is a mode of communication and an educational practice, which calls upon the narration of experiences, knowledge, beliefs, values, etc. In the text, we relay this narrative, which specifically includes courses of action, practices, and experiences, recounted as beneficial learning, and from which several analyzes emerge. Shared reflections allow us to move forward on this path of reconciliation and decolonization of education, even within Indigenous schools.